The legal status of physiotherapists’ profession - Mełgieś, Katarzyna (Polish Journal of Public Health, 2018)
Physiotherapy is a discipline of clinical medicine, using its own diagnostic and therapeutic methods, including the treatment of movement and physical stimuli. The new legal regulations resulting from the Act of 25 September 2015 on the Profession of Physiotherapy have granted a special professional status to this group of specialists, what results from the fact that it is recognized as an independent medical profession. It should be noted, however, that the introduced law, although expected for many years, did not stabilize the legal situation of this professional group until the end. There are still doubts of a juridical nature which make it difficult to provide unambiguous answers to the basic questions regarding the legal status of physiotherapists as persons performing an independent medical profession. This publication, referring to the applicable statutory regulations and views presented in the legal doctrine, analyzes the current legal status, indicates the weaknesses of the adopted legislative solutions and avoids the changes